Seven‐Step Synthesis of All‐Nitrogenated Sugar Derivatives Using Sequential Overman Rearrangements. (28th January 2021) - Okuyama, Yuya; Kidena, Mayu; Kato, Erina; Kawano, Sayaka; Ishii, Koki; Maie, Kenta; Miura, Kazuki; Simizu, Siro; Sato, Takaaki; Chida, Noritaka
Abstract: All‐nitrogenated sugars (ANSs), in which all hydroxy groups in a carbohydrate are replaced with amino groups, are anticipated to be privileged structures with useful biological activities. However, ANS synthesis has been challenging due to the difficulty in the installation of multi‐amino groups. We report herein the development of a concise synthetic route to peracetylated ANSs in seven steps from commercially available monosaccharides. The key to success is the use of the sequential Overman rearrangement, which enables formal simultaneous substitution of four or five hydroxy groups in monosaccharides with amino groups. A variety of ANSs are available through the same reaction sequence starting from different initial monosaccharides by chirality transfer of secondary alcohols. Transformations of the resulting peracetylated ANSs such as glycosylation and deacetylation are also demonstrated. Biological studies reveal that ANS‐modified cholesterol show cytotoxicity against human cancer cell lines, whereas each ANS and cholesterol have no cytotoxicity. Abstract : Concise synthesis of all‐nitrogenated sugar derivatives was achieved in seven steps from commercially available monosaccharides. The sequential Overman rearrangement enabled formal simultaneous substitution of four or five hydroxy groups in the monosaccharides with amino groups. A variety of ANSs were available by the same synthetic route starting from different carbohydrates. Transformation and biological activities of ANS derivatives were also reported.